(untitled) (Nordic Journal of Practical Theology, 2022)
This article presents the project Pastoral Care and Community building work among young people (SOFA) and findings from the project’s three sub-studies. These studies are described in separate articles in this issue. Themes related to relationships and identity, faith and meaning, trauma and shame, sex and drugs, and personal and social difficulties were identified as addressed in the practice of pastoral care for adolescents. The project is rooted in the practical-theological research environment at MF University College, and has been carried out in collaboration with active caregivers in church youth environments. The project aims to contribute to the development of Nordic practical theology, in the intersection between the practice fields of pastoral care and youth ministry. The project places itself within the new directions within empirical research on practical theology that go under the heading «practice matters.» It is in the span between the ideals of faith education and the experiences from church youth arenas that the SOFA project explores pastoral care practices and community-building work among young people.